Sintesis Katalis Perovskite Komposit CeFeO3/SBE Dengan Metode Sol-Gel Untuk Proses Degradasi Fotokatalitik Pewarna Tekstil Methylene Blue - Marihot Danield Vyendri Simatupang; Edy Saputra; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Perovskite catalyst composite of cerium ferrite (CeFeO3) have been successfully prepared via assembling mesoporous CeFeO3 on the surface of spent bleaching earth (SBE) with citricacid assisted sol-gel method. Physical properties were characterized by several techniques such as X-ray diffraction (XRD) and nitrogen gas adsorption-desorption (BET), absorbanceof oxidation samples were analysis using UV-Vis spectrophotometer measurement. The activity of CeFeO3/SBE catalyst was evaluated by the photocatalytic degradation ofmethylene blue (MB) in aqueous solutions under visible light irradiation. Effect the type of supports (SBE extraction and calcination resulted), catalyst concentrations (0.5-1.5 g/L), pH(5.0, 7.0, 9.0 and 11.0) and initial concentrations of MB (10-40 mg/L) were investigated in this research. Result indicating that CeFeO3/SBE extraction exhibited remarkablephotocatalytic degradation activity with the overall removal of MB up to 99.20% within 135 minutes at the conditions of 10 mg/L methylene blue, 1.0 g/L catalyst and pH 7 (neutral).Therefore, the CeFeO3/SBE is a very promising photocatalyst in future industrial application to treat effectively wastewater of dyes.Keywords: cerium ferrite, methylene blue, perovskite, photocatalytic, wastewater